Sentiment Analysis untuk Mengidentifikasi Faktor Penunjang Kesuksesan Feeder Wira Wiri Suroboyo - Bellanov, Agrienta; Irawati, Desrina Yusi (Universitas Sarjanawiyata Tamansiswa, 2025)
Traffic congestion is a major issue in Surabaya, a metropolitan city with a high rate of private vehicle growth. To address this problem, the Surabaya city government launched the Wira Wiri Suroboyo feeder service as a complement to the Suroboyo Bus mass transportation system. This study aims to identify public responses to the service through sentiment analysis of comments posted on the official Instagram account @wirawirisuroboyo. The methodology employed sentiment analysis and text mining techniques using R Studio software. Data were collected via web scraping from 230 comments and processed through data cleaning, tokenization, case folding, and stopword removal. The results show that 37% of comments were positive, 16% expressed trust, 10% were sad, and 8% were negative. A word cloud revealed dominant words such as